2019
DOI: 10.1186/s11658-019-0194-5
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen stimulates SREBP2 expression in hepatic cell lines via an estrogen response element in the SREBP2 promoter

Abstract: ObjectiveHypoestrogenism in women is strongly associated with menopause and it can lead to lipid disorder, which predisposes people to premature cardiovascular disease. However, the mechanism of lipid disorder remains unclear. Sterol regulatory element-binding protein 2 (SREBP2) is the key transcription factor regulating cholesterol metabolism. We hypothesize that estrogen regulates SREBP2 transcription through an estrogen response element (ERE) in the SREBP2 promoter region.MethodsHuman hepatoblastoma cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Negative associations of E2 with TC and LDL-C has been demonstrated in ERα-deficient models, women with E2 deficiency and postmenopausal women on E2 treatment ( 59 65 ), results consistent with our study findings. These protective effects of E2 can be largely attributed to its upregulation of low-density lipoprotein receptors (LDLR) on hepatic cells: 1) through nuclear receptor ER, E2 stimulates the expression of transcription factors related to cholesterol metabolism, which upregulates LDLR expression as a downstream target ( 66 ); 2) through G protein-coupled estrogen receptor, E2 prevents PCSK9-dependent LDLR degradation, thus reducing the levels of TC and LDL-C as well ( 67 ). In terms of gonadotropins, although studies regarding the role of LH in dyslipidemia are scarce, several previous studies addressing the links between FSH and lipid levels in postmenopausal women have demonstrated that higher FSH in postmenopausal women was related to higher levels of both TC and LDL-C, with stronger relations seen in younger compared to older postmenopausal women, which were close to the results of our results ( 29 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Negative associations of E2 with TC and LDL-C has been demonstrated in ERα-deficient models, women with E2 deficiency and postmenopausal women on E2 treatment ( 59 65 ), results consistent with our study findings. These protective effects of E2 can be largely attributed to its upregulation of low-density lipoprotein receptors (LDLR) on hepatic cells: 1) through nuclear receptor ER, E2 stimulates the expression of transcription factors related to cholesterol metabolism, which upregulates LDLR expression as a downstream target ( 66 ); 2) through G protein-coupled estrogen receptor, E2 prevents PCSK9-dependent LDLR degradation, thus reducing the levels of TC and LDL-C as well ( 67 ). In terms of gonadotropins, although studies regarding the role of LH in dyslipidemia are scarce, several previous studies addressing the links between FSH and lipid levels in postmenopausal women have demonstrated that higher FSH in postmenopausal women was related to higher levels of both TC and LDL-C, with stronger relations seen in younger compared to older postmenopausal women, which were close to the results of our results ( 29 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The short estrus phase can be influenced by triterpenoid and saponin compounds contained in the ethanol extract of papaya leaves by hormonal disturbances (Hakameri et al, 2020). Triterpenoids and saponins can bind to estrogen receptors and trigger interactions with Estrogen Response Element (ERE) in triggering the expression of estrogen responsive genes in estrogen synthesis (Men & Zong., 2019). Increased levels of estrogen in the blood that are too high can cause negative feedback, thereby suppressing the ovulation mechanism (Jain et al, 2015;Zhang et al, 2020).…”
Section: Estrus Cyclementioning
confidence: 99%
“…Likewise, pathway analysis of the liver proteome from a subset of individuals indicates overrepresentation of proteins involved in cholesterol biosynthesis (GO:0045337; FDPS and HMGCS1); we confirmed upregulation of SREBP‐2 and its main targets (ie, HMGCS1 and HMGCR) in the entire cohort. Because estrogen regulates Srebp‐2 transcription through an estrogen response element, 62 our finding of upregulated Esr1 in liver of IVF‐females, suggests that estrogen dynamics are altered in IVF‐females in a way that contributes to dysregulation of cholesterol homeostasis. Our findings lay the groundwork for further interrogating the estrogen‐SREBP‐2 relationship and the interrelated metabolic, endocrine and reproductive effects.…”
Section: Discussionmentioning
confidence: 84%